Computational physicochemical analysis and production of OmpA's mutants with functional potential in drug delivery (2020)
In recent years, pharmaceutical field has been searching for sustainable drug delivery vehicles to treat persistent medical conditions and diseases. This project seeks to perform a physicochemical analysis for OmpA's mutants (mutant 6 and mutant 12) in order to verify their viability as transport vehicles for drug delivery. For this objective, numerous computational programs were used (I-TASSER, Swiss Model, Chimera and ExPASy Bionformatics Resource Portal) to determine physicochemical, structural and translocation properties for both mutants. On the other hand, this project pursues to standardize the methodology for expression, quantification and purification of the mentioned mutants. The above with the aim of designing a replicable process that guarantees the target proteins production. The methodology for mutants'production was based in transferring synthetized genes sequences from pUC-57 plasmid to pET6xHN-N cloning vector through digestion, ligation and transformation protocols in Escherichia coli strains. Additionally, purification and quantification process for mutant 6 was developed following affinity chromatography column and SDS page techniques. This procedure was unclear in terms of a successful purification because in polyacrylamide gel only appeared a low-resolution trace of the target bands, instead of high- resolution bands that confirm an effective purification. The results showed that both mutants have physicochemical properties (cationic- charged surface, amphipathic condition, high solubility in water and thermostability) and protein structures (an anti-parallel ? sheet that composed the secondary structure) that allow to predict an effective translocation of the cell membrane. Besides, the production pathway proposed was effective, but purification and quantification processes should be modified for obtaining more accurate results